MON-386 Determining Vitamin D Status: Analytical Variability Between Available Assays - Wahab, Azni Lihawa Abdul (J Endocr Soc, 2020)
Clinical interest to evaluate serum 25-hydroxyvitamin D[25(OH)D] to assess Vitamin D status in health risks continue to increase exponentially over the last decade. Variability of 25(OH)D measurements remains controversial despite the international initiative Vitamin D Standardization Program (VDSP) to standardise the assays. The aim of the present study was to examine the correlation of 25(OH)D concentrations measured by different assays. We measured 25(OH)D using the new Abbott Alinity and DiaSorin LiaisonXL chemiluminescence immunoassays against the National Institute of Standards and Technology (NIST)-traceable liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. The immunoassay method were compared with the LC-MS/MS using Passing-Bablok regression and Bland-Altman analysis. Common 25(OH)D cut-point for classification of vitamin D deficiency was used to compare the different assays. 125 adult serum samples were randomly selected and measured 25(OH)D levels ranged between <10 nmol/L to 290 nmol/L as determined by LC-MS/MS. Compared to the LC-MS/MS, both immunoassays demonstrated strong positive relationship based on Passing-Bablok regression analysis. The results were as follows: Abbott Alinity = 0.85x + 1.29nmol/L, 95% CI: -2.39 to 5.03 (r=0.94); DiaSorin LiaisonXL= 0.74x + 2.54nmol/L, 95% CI: -2.53 to 6.18 (r=0.91). Despite apparent good correlation, the overall mean bias was -12.6% for Abbott Alinity and -24.4% for DiaSorin LiaisonXL assays. A higher percentage of patients were classified as vitamin D deficient (25(OH)D <50 nmol/L) using DiaSorin LiaisonXL (53%) followed by Abbott Alinity (49%), when compared with LC-MS/MS (34%). Using 25(OH)D ≥ 50nmol/L as “adequate” determined by LC-MS/MS method, 22% (18/82) and 28% (23/82) of patients were classified as “deficient” when analysed on Abbott Alinity and DiaSorin LiaisonXL respectively. Clinician should be aware of the inter-method variability among different Vitamin D assays despite standardization efforts. These differences could be due to cross‐reactivity with 25(OH)D(2) and vitamin D metabolites, such as 24,25(OH)(2)D and epimeric forms. 3‐epi‐25(OH)D is not separated chromatographically by the LC-MS/MS method used in this study. Therefore, the negative bias observed might be due to interference from the 3‐epi‐25(OH)D, whereby clinical significance is uncertain. It is present in low concentrations in adult human serum, (1) but seen in significant amounts in neonatal serum.(2) It is advisable to monitor serum 25(OH)D level following treatment in the same laboratory. 1. Lensmeyer G, et al. The C-3 epimer of 25-hydroxyvitamin D3 is present in adult serum. JCEM 2012; 97: 163–8. 2. Singh RJ, et al. C-3 epimers can account for a significant portion of total circulating 25-hydroxyvitamin D in infants, complicating accurate measurement and interpretation of vitamin D status. JCEM 2006; 91: 3055-61.